The (K-, π+)Σ- - hypernuclear production in flight - Petridou, Th.; Daskaloyannis, C. (HNPS Advances in Nuclear Physics, 2019)
The in-flight (K-,π+) Σ -hypernuclear spectra are studied, using a simple interaction model with a square well central part and a delta function spin-orbit Σ-nuclearcore interaction. A comparison is made between the theoretical results and the in-flight (Α’ ,π+) experimental data for 12Σ C, 16Σ Ο and 6Σ Li. A shallow potential, with a central potential depth of Vc = (-5 - il5)MeV and a spin-orbit depth of Vao = lbMeV, gives a satisfactory representation of the CERN and BNL in-flight data.